When the world stumbled COVID-19 and the failure of the international system (2020)
In the first half of March 2020, the borders of the United States of America slammed shut. They had already begun to close in January, when President Donald Trump’s administration announced restrictions on visitors from China, a “ban” that was late, chaotic, and incomplete. In fact, tens of thousands of travelers continued to arrive in the United States from China every day, including from Wuhan, where the novel coronavirus had originated.1 Six weeks later, the closures were hardly much smoother. Without warning its European allies, the United States abruptly announced impending restrictions on travelers from Europe, producing a rush to get home that led to higher rates of coronavirus infection inside the United States.2 Passengers who knew they were ill got on planes, afraid of being stranded. Many were stuck standing for hours in crowds at airports and at security checkpoints.